Relationship between nutritional status and other factors with the incidence of hypercholesterolemia in adults in Cikupa - Nunung Cipta Dainy; Aulia Nakhlah Narapati (Sarana Ilmu Indonesia (salnesia), 2024)
The prevalence of hypercholesterolemia in Tangerang Regency, the prevalence of hypercholesterolemia based on a total cholesterol concentration of >200 mg/dl is 39,8%. The research aims to determine the description of nutritional status, physical activity, habits of eating fatty foods and fat intake with the incidence of hypercholesterolemia in adults in Cikupa Village. This research is observational with a cross sectional research design. The number of respondents was 61 people using accidental sampling technique. The data taken includes data on body weight, height, nutritional intake, frequency of eating fatty foods, physical activity and total cholesterol levels. The research instrument used a food recall questionnaire, FFQ, and PAL. Bivariate analysis uses the chi-square test. The results of the prevalence of hypercholesterolemia in the adult group in Cikupa were 59,4%. Most of them had normal nutritional status (77,6%), light physical activity (71,6%), often consumed fatty foods (44,8%) and a higher fat intake of (53,7%). There was no significant relationship between nutritional status, physical activity, eating habits of fatty foods, and fat intake with hypercholesterolemia in the adult group in Cikupa Village (p>0,05).